Food safety knowledge, attitude and practices of orange fleshed sweetpotato puree handlers in Kenya - Malavi, D.N.; Abong, G.O.; Muzhingi, T. (2017)
Orange Fleshed Sweetpotato (OFSP) puree is a nutritious food ingredient for promoting Vitamin A intake in processed food products in Sub-Saharan Africa (SSA). OFSP puree handlers play an important role in ensuring production of consistently safe and quality OFSP puree and related processed products. Lack of or insufficient knowledge on food safety coupled with poor practices by food handlers are major causes of foodborne illnesses and deterioration in food quality along the food chain. The current study assessed levels of food safety knowledge, attitude and hygiene practices (KAP) of OFSP puree handlers in Kenya. A cross-sectional study using a self-administered structured questionnaire was conducted among 35 OFSP puree handlers chosen by exhaustive sampling during the period of July and August 2016. The mean percentage scores for knowledge, attitude, practices and overall KAP were 73, 89, 80 and 81, respectively. OFSP puree handlers in this study had low level of knowledge on personal hygiene, food contamination, foodborne illnesses, cleaning and sanitation with mean scores of 80, 64, 76 and 63%, respectively. Training had a significant impact on knowledge (p=0.020), attitude (p=0.050), practices (p=0.006) and overall KAP (p=0.001) with majority of the OFSP puree handlers (63%) having received a training on food safety. A significant moderate positive correlation existed between knowledge and practices (r=0.358, p=0.035) and attitude and practices (r=0.42, p=0.013). As per adjusted linear regression analysis, food safety practices significantly (p=0.045) increased by 0.32% with one percent increase in knowledge and by 0.38% (p=0.018) with one percent increase in attitude. OFSP puree handlers had low level of knowledge and practices but demonstrated a positive attitude on food safety. Frequent food safety training is needed to improve knowledge and hygienic practices of OFSP puree handlers.